2019
DOI: 10.1111/pin.12811
|View full text |Cite
|
Sign up to set email alerts
|

Cten promotes Epithelial–Mesenchymal Transition (EMT) in colorectal cancer through stabilisation of Src

Abstract: Cten is an oncogene promoting EMT in many signaling pathways, namely through Snail. We investigated whether Cten function could be mediated through Src. Cten levels were modulated by forced expression in HCT116 and gene knockdown in SW620 CRC (colorectal cancer) cell lines. In all cell lines, Cten was a positive regulator of Src expression. The functional importance of Src was tested by simultaneous Cten overexpression and Src knockdown. This resulted in abrogation of Cten motility‐inducing activity and reduct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 25 publications
0
15
0
Order By: Relevance
“…Thorpe et al (13) demonstrated that CTEN may facilitate epithelial-mesenchymal transition (EMT) processes by preventing the degradation of Snail protein in colorectal cancer. Asiri et al (14) demonstrated that CTEN is a positive modulator of Src, and that CTEN may promote EMT and metastasis via post-transcriptional stabilization of Src protein in colorectal cancer. Notably, Hong et al (15) revealed that a proportion of nuclear-localized CTEN contributes toward cell proliferation in cancer cells.…”
Section: Discussionmentioning
confidence: 99%
“…Thorpe et al (13) demonstrated that CTEN may facilitate epithelial-mesenchymal transition (EMT) processes by preventing the degradation of Snail protein in colorectal cancer. Asiri et al (14) demonstrated that CTEN is a positive modulator of Src, and that CTEN may promote EMT and metastasis via post-transcriptional stabilization of Src protein in colorectal cancer. Notably, Hong et al (15) revealed that a proportion of nuclear-localized CTEN contributes toward cell proliferation in cancer cells.…”
Section: Discussionmentioning
confidence: 99%
“…It was recently shown that the oncoprotein Src in endosomal membranes promoted exosome secretion and tumor progression [186]. Consistently, Src promotes EMT triggered by multiple EMT inducers including EGF [187], leptin [188], Cten [189], and δNp63γ [190]. Anti-EMT strategies involving targeting the TGFβ receptor or CDK2 may inhibit exosome/oncosome release from cancer cells [36].…”
Section: Exosomal Drug Resistancementioning
confidence: 93%
“…Formation of these structures enables cells to migrate and contributes to invasion and metastasis of tumor cells [17]. Among tensins, tensin-4 is mainly reported as a molecule participating in EMT through various signaling pathways such as Ras/Raf/extracellular signal-regulated kinase (ERK), TGF-β, Akt/PI3K, and signal transducer and activator of transcription 3 (STAT3) and growth factors-related pathways [13,[18][19][20][21].…”
Section: Functions and Mechanism Of Action Of Tensinsmentioning
confidence: 99%